Aspects regarding the relationship between technical training and somatic, functional and motor parameters, at handball players - Batiurea, E.; Stan, Z.; Rizescu, C. (Science, Movement & Health, 2014)
Purpose. The purpose of this study is to observe the influence of somatic, functional and motor parameters upon the game's technique, at senior handball players. On the second place, correlations were made between the somatic and functional parameters and the motor ones. Methods. The study was performed on 30 athletes aged between 19 and 31 years old (M = 24.2, SD = 3.23). There were applied 31 tests, as follows: technical (30m dribbling among poles, Throwing the ball from distance, Throwing the ball towards the wall and recatching it - version I and II, Throwing the ball at a fixed target - version I and II, Slalom dribbling), somatic (height, wingspan, hand length, thoracic perimeter, chest elasticity, weight), functional (the heart rate, the breathing rate, the vital capacity, the Lorentz resistance index, the Ruffier test, the Sargent test) and motor (5x30m, triangle movement, "the combined", long jump from a stationary position, detent, penta-jump, abs, 2x400m, 800m, sprint test). Results. From the 257 correlations between these variables, the value for r . 40% was recorded for 51 of them. The rarest correlations were found between somatic parameters and technical parameters (4), functional parameters and technical parameters (4), but also between functional parameters and motor parameters (3). Most correlations are between technical parameters and motor parameters (30). Conclusions. The training for developing technical executions is based on improving the motor behavior of athletes that gives them many opportunities to solve unexpected situations that arise during a match. This concept is demonstrated by the close connection between the technical parameters and the motor ones (30 correlations, where r has values between 41% and 78%). As the results show, the technical test results are the most influenced by the level of abdominal strength development and speed running, while functional variables have a weak influence on motor and technical skills, in our case. The somatic parameters, although they have an insignificant direct influence on the technique, they manifest more strongly in the case of motor skills. These conclusions should be accepted with care, as it concerns only this group of athletes, while the obtained correlations indicate the degree of association between the used variables and not the cause of those connections.